PENERAPAN NILAI-NILAI PANCASILA DALAM MENINGKATKAN JIWA NASIONALISME SISWA - Noviati, Noviati; Dian Iva Prestiana, Novita; Maysaroh Chairunnisa, Nurlaila (Universitas Islam 45 Bekasi, 2023)
Pancasila education must be able to answer the question of how best to foster nationalism among Indonesian people. Strategies are needed to strengthen nationalism by applying the ideals of the state ideology Pancasila and nationalism which is experiencing a decline along with the increasing number of other cultures that are increasingly popular among Indonesians. Protecting Pancasila can be done by providing information on Pancasila according to grade level to primary school students. To instil the ideals of Pancasila to elementary school students and ensure that these ideals are maintained and fostered so that later they can give birth to brilliant ideas or ideas, teaching can be done because children at this age already have definite and logical concepts. The results of community service activities in the form of 90% can know and answer together with enthusiasm from the questions given by students ranging from examples of values from the first precept to the fifth precept.